KEIGO KEIGO DALAM DRAMA SARIES コーヒー&バニラ - made_lady_aridayani24 made_lady_aridayani24 (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2024)
This article discusses keigo in the drama series コーヒー&バニラ “Coffee&Vanilla” by Yuko Shimoda and Sorami Date. The method used in this study was the method of observing and noting. Listening to the series drama entitled コーヒー&バニラ “Coffee&Vanilla” and then criticizing the keigo that appears in the series drama, analyzing the use of keigo and the factors influencing the use of keigo in the series drama entitled コーヒー&バニラ “Coffee&Vanilla”. This research refers to Tsujimura's theory (1991) about keigo and Mizutami's theory (1998) about the factors influencing the use of keigo respects. Based on the results of the study, it can be concluded that in the series drama entitled コーヒー&バニラ “Coffee&Vanilla” there is more use of teineigo to soften the words between the speaker and the interlocutor. The results of the study found four words using teineigo. Three words to use songkeigo and 1 word to use kenjougo.